PENGARUH SUPERVISI AKADEMIK DAN IMPLEMENTASI ASPEK PEDAGOGIK TERHADAP KINERJA MENGAJAR GURU PAUD SE-KECAMATAN LUAK KABUPATEN LIMA PULUH KOTA - -, Suryati (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This research aims to examine and analyze the effect of academic supervision andimplementation of pedagogy aspect toward teaching performance of kindergarten teacher inLuak, Limapuluh Kota district. The hypothesis are; 1) academic supervision has significanteffect toward teaching performance, 2) implementation of pedagogy aspect has significanteffect toward teaching performance, 3) academic supervision and implementation of pedagogyaspect simultaneously have significant effect toward teaching performance.The sample of this research are 50 kindergarten teachers in Luak, Limapuluh Kota district.This research uses multiple regression technique with software SPSS to examine the relationand effect of dependent and independent variables.The result shows that academic supervision has significant effect toward teaching performanceof kindergarten teacher, the implementation of pedagogy aspect has significant effect towardteaching performance of kindergarten teacher. Simultaneously, those variables havesignificant effect toward teaching performance of kindergarten teacher, the percentage is68,10%. Both of variables have important role and contribution toward teaching performance, but there are other factors that not discussed in this research. The teaching performance ofteacher can be rised by upgrading academic supervision and implementation of pedagogyaspect effectively.Keywords : supervision, pedagogy, teaching performance.